Abnormal reoxidation effects in Ba‐excess La‐doped BaTiO3 ceramics prepared by the reduction‐reoxidation method. Issue 7 (3rd April 2017) - Zu, Hao; Chen, Tao; Gao, Chao; Fu, Qiuyun; Zhou, Dongxiang; Hu, Yunxiang; Zheng, Zhiping; Luo, Wei
Abstract: Ba‐excess La‐doped BaTiO3 ceramics have been successfully applied to prepare laminated chip thermistor. Ceramics were firstly fired in a high‐purity N2 flow and then reoxidized in air to obtain positive temperature coefficient of resistivity effect. However, an abnormal reduction trend of room‐temperature (RT) resistivity was found to be always beginning at ~800°C during reoxidation. This anomaly was found closely correlated with the insulating second phase (Ba2 TiO4 ) at grain boundary, which destroyed conducting pathways between semiconducting BaTiO3 grains. When reoxidation temperature was up to ~800°C, the insulating Ba2 TiO4 could be gradually consumed and then conducting pathways reestablished leading to RT resistivity reduction. To further prove the proposed explanation, the reoxidation effects of TiO2 ‐added ceramics were also studied, in which no Ba2 TiO4 existed and certainly the abnormal RT resistivity reduction disappeared.